MEASURING VIBRATION AT TRACTOR PLATFORM , STEERING WHEEL AND SEAT EFFECTIVE AMPLITUDE TRANSMISSIBILITY FACTOR DURING OPERATION TILLAGE - Al-Mafrachi, A. A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment conducted to measure vibrations on three axes longitudinal X, lateral Y and vertical Z on steering wheel, platform tractor and vertical vibration in seat tractor and seat effective amplitude transmissibility (SEAT) factor during operation tillage in silt clay loam soil with depth 18 cm in Baghdad. Split – split plot design under randomized complete block design with three replications least significant design 5 % used. Three factor were used in this experiment included two types of plows included chisel and disc plows which represented main plot, three tires inflation pressure was second factor included 1.1 ,1.8 and 2.7 bar, and three forward speeds of the tillage was third factor included 2.35 , 4.25 and 6.50 km/hr. Results showed disc plow recorded higher vibration values for three axes X,Y and Z on platform, steering wheel and vertical vibration seat tractor. No significant effect between chisel and disc plows in (SEAT) Factor. Tier pressure 2.7 bar recorded higher vibration values in all measurements. Speed tractor 6.50 km/hr recorded higher vibration values in all measurements. Vibration values increasing when increasing tiers inflation pressure and tractor speed. All interaction among treatments significant. Level of vibration in these experiment a cross legislated permissible vibration exposure limits in the world except  the vibration transmitted to steering wheel and tractor seat during tillage under 1.1 bar and tractor speed 2.35 km/hr.